The COVID-19 Pandemic: A Comprehensive Review of Global Impacts and Mitigation Strategies - Billy Coen (Global Writing Academica Researching & Publishing, 2023)
The COVID-19 pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), emerged as a global health crisis in late 2019 and quickly spread across continents, disrupting societies, economies, and healthcare systems worldwide. This article provides a comprehensive review of the COVID-19 pandemic's origins, epidemiology, clinical manifestations, global impacts, and the various strategies implemented to mitigate its spread. Additionally, it analyzes the lessons learned from this unprecedented event, highlighting the importance of international cooperation, preparedness, and evidence-based interventions to combat future pandemics.